Analisis Pelaksanaan Peran, Fungsi dan Wewenang Governing Body, dan Direktur di Rumah Sakit Dalam Upaya Peningkatan Manajemen Mutu - Rudiansyah Rudiansyah; Joni Herman; Wagiran Wagiran; Aditiya Sardi; Abil Rudi; Akhmad Hasan; Nurul Khoirun Nisa; Ria Damayanti; Sohibun Sohibun (LPPM Institut Pendidikan Nusantara Global, 2025)
Healthcare services in hospitals involve a high level of complexity, making them prone to conflicts both within and outside the institution. The implementation of quality management still faces numerous obstacles, as evidenced by the lack of staff awareness regarding quality management, frequent conflicts, and unclear coordination, communication, and information pathways. This study aims to analyze the implementation of the roles, functions, and authorities of the governing body and the hospital director in quality management practices. The research design uses a descriptive method with a qualitative approach. The main informants are the governing body and the hospital director, while the triangulation informants include attending physicians, nurses, and the quality team leader. Data were collected through in-depth interviews and analyzed using content analysis. The results show that while the roles and functions of the governing body have been implemented, its authority has not been fully optimized. Likewise, the roles and authority of the director have been carried out, but the functions have not been optimally implemented. The study recommends allocating a budget for off-site training, creating guidelines for documentation and reporting, developing performance evaluation manuals, preparing evaluation checklists, and establishing internal satisfaction assessments.